1990
DOI: 10.1002/j.1460-2075.1990.tb07591.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of replication of plasmid R1: formation of an initial transient complex is rate-limiting for antisense RNA-target RNA pairing.

Abstract: The replication frequency of plasmid R1 is determined by the availability of the initiator protein RepA. Synthesis of RepA is negatively controlled by an antisense RNA, CopA, which forms a duplex with the upstream region of the RepA mRNA, CopT. We have previously shown that the in vitro formation of the CopA‐CopT duplex follows second‐order kinetics and occurs in at least two steps. The first step is the formation of a transient (kissing) complex, which is subsequently converted to a persistent duplex. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 23 publications
5
60
1
Order By: Relevance
“…Interaction of such highly structured antisense RNA molecules with their targets is likely to involve several steps and starts with the formation of so-called kissing complexes between the singlestranded loops of antisense and target RNA. This concept was initially proposed by for the interaction of RNAI and RNAII of ColEl and was later supported by both in vivo and in vitro studies of the interaction of the CopA antisense RNA of plasmid R1 with its target CopT (31)(32)(33). In vitro experiments with the R1 system even suggested that formation of the kissing complex is sufficient for the inhibitory action of CopA to occur (43).…”
Section: Materlils and Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Interaction of such highly structured antisense RNA molecules with their targets is likely to involve several steps and starts with the formation of so-called kissing complexes between the singlestranded loops of antisense and target RNA. This concept was initially proposed by for the interaction of RNAI and RNAII of ColEl and was later supported by both in vivo and in vitro studies of the interaction of the CopA antisense RNA of plasmid R1 with its target CopT (31)(32)(33). In vitro experiments with the R1 system even suggested that formation of the kissing complex is sufficient for the inhibitory action of CopA to occur (43).…”
Section: Materlils and Methodsmentioning
confidence: 89%
“…The topological organization of the replication region of pIP501 exhibits similarity to that of the gram-negative plasmid R1 (6,26). Synthesis of the RepA initiator protein of R1 is also controlled by an antisense RNA complementary to the leader region of the repA mRNA (26,32,33). It has, however, recently been found that the CopA antisense RNA of R1 acts at the translational level rather than on transcription.…”
Section: Materlils and Methodsmentioning
confidence: 99%
“…Previous kinetic and mutational analyses showed that binding is initiated via a loop-loop interaction between the 59-CGCC-39 sequence in the hairpin loop of CopA and the complementary sequence of CopT (Persson et al+, 1988(Persson et al+, , 1990b)+ However, these initial interactions are transient, as the present study of CopA-CopT and CopI-CopT complexes shows that most of the nucle- -H2), or in the presence of CopT-H2 (ϩ CopT-H2)+ Lanes U, L: RNase U2 and alkaline ladders, respectively+ C: Effect of magnesium concentration on Pb 2ϩ hydrolysis+ The intensity of the band corresponding to cleavage at U47 of CopI-H2 complexed to CopT-H2 is depicted as a function of magnesium concentration+ otides in loop II of the antisense RNA, as well as in the complementary target loop, are accessible to singlestrand-specific probes+ Thus, helix extension from this initial loop-loop complex generates helices B and B9, resulting in disruption of the initiating base pairs and formation of the extended kissing complex (Fig+ 6C)+ The enzymatic and chemical probing data indicate that nucleotides on both sides of the upper stem II segments (48-56, 63-68) of CopA and CopI interact by interstrand pairing with the complementary nucleotides in CopT forming the two intermolecular helices B and B9 (Fig+ 6C)+ Further support comes from the observation that mutations in helices B/B9 that disrupt the complementarity between CopA or CopI and CopT affect the structure of the extended kissing complex+ On the other hand, mutations below the lower bulge had no effect on the formation of helices B and B9+ Taken together, these results define the boundaries of helices B and B9 (Fig+ 6C) and indicate that progression of the intermolecular helices B and B9 is arrested due to topological stress+ Consequently, the intramolecular helices A and A9 remain identical in CopI-CopT and CopACopT complexes+ We infer that conversion of the initial loop-loop interaction to the four-helix junction structure is facilitated by low stability of the upper stem regions, conferred by the bulged residues and the presence of several G-U and A-U base pairs in both RNAs+ By independent experiments, it was previously shown that removal of bulges severely impaired binding rates and in vivo control (Hjalt & Wagner, 1995)+ The results presented here also indicate that complete pairing between CopA and CopT does not occur rapidly in vitro+ It is likely that the formation of the peculiar four-helix junction structure results in kinetic or topological entrapment of the complex for extended periods of time (Malmgren et al+, 1997; this work)+ The extended kissing complex adopts an X-shaped structure with a side-by-side alignment of helical domains Molecular modeling was used to deduce a global fold of the stable CopA-CopT complex+ The validity of the overall architecture presented relies on a variety of experimental data (chemical and enzymatic probing; effect of mutations on CopA-CopT structure) that were used to assemble a structure with appropriate stereochemistry+ We propose that the folding of the extended kissing complex at the four-way junction adopts an asymmetric stacked cruciform structure, formed by the colinear helices B-A and B9-A9 in a parallel configuration (Figs+ 6C and 7)+ This model predicts a close contact between helices at the stacked cruciform junction (Fig+ 7)+ Such a negatively charged cavity is likely to bind divalent ions with high affinity+ Interestingly, computer modeling based on Brownian-dynamics simulations (Hermann & Westhof, 1998) predicted a magnesium-binding site coordinated via the phosphate groups betwee...…”
Section: Conversion Of a Loop-loop Interaction To A Four-helix Junctionmentioning
confidence: 99%
“…CopA binds to the leader region of the repA mRNA (CopT), located about 80 nt upstream of the repA start codon (Fig+ 1)+ Binding prevents tap translation and thereby repA expression (Blomberg et al+, , 1994Malmgren et al+, 1996)+ The CopA-CopT binding process is viewed as a series of reactions leading to progressively more stable complexes (Persson et al+, 1988(Persson et al+, , 1990a(Persson et al+, , 1990bMalmgren et al+, 1997)+ CopA and CopT are fully complementary and both RNAs contain a major stem-loop structure (II/II9 in Fig+ 1) that is essential for high pairing rates and control (Öhman & Wagner, 1989;Hjalt & Wagner, 1992, 1995+ The initial step involves a transient looploop interaction (kissing complex) between the complementary hairpin loops (Persson et al+, 1990a(Persson et al+, , 1990b)+ Indeed, a truncated CopA (CopI, Fig+ 1), lacking the 59 proximal 30 nt and consisting only of the major stemloop, does not form stable duplexes with CopT, but is capable of competing with CopA for binding (Persson et al+, 1990b)+ It was recently shown that in both CopICopT and CopA-CopT complexes, initial kissing is rapidly followed by more extended intermolecular interactions (Malmgren et al+, 1997)+ Subsequently, the single-stranded region in the 59 tail of CopA pairs with its complement in CopT to yield the stable, inhibitory CopA-CopT complex+ This complex is the dominant product of binding in vitro (Malmgren et al+, 1996(Malmgren et al+, , 1997+ Complete duplex formation is very slow and has been proposed to be irrelevant for control (Malmgren et al+, 1996(Malmgren et al+, , 1997Wagner & Brantl, 1998)+ Different pairing pathways that result in rapid formation of stable antisense-target RNA complexes have been described (Kittle et al+, 1989;Persson et al+, 1990b;Tomizawa, 1990;Siemering et al+, 1994;Thisted et al+, 1994)+ A common feature is the use of a restricted single-stranded region in each interacting RNA for the initial step+ In most cases, binding initiates between two loops, in some cases between a loop and a singlestranded RNA segment+ Subsequently, more stable complexes are either formed by the pairing of distal RNA segments or, in the latter case, by extension of the first helix+…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation